Team Ownership and Philanthropy in Professional Sport: A Perspective on Organizational Generosity - Babiak, Kathy; Yang, Daniel (Frontiers in Sports and Active Living, 2022)
Corporate philanthropy (CP) is a vehicle for businesses to create a social impact in communities where their operations are located. An overlooked aspect of this phenomenon is the role and function played by CP influencers within firms—particularly organizational principals/owners. Using an upper echelons perspective, this study explores the relationship between team ownership and the level of CP in the professional sport context. To this end, longitudinal data of philanthropic giving of 94 U.S. professional sport teams in the NBA, NFL, MLB, and NHL were collected. We also collected team owner characteristics such as individual/family ownership, age, tenure as team owner, other charitable work, educational background, and connection to community from a variety of publicly available sources. The findings revealed that team owner age, ownership tenure, and previous philanthropic involvement contributed to increased charitable giving in professional sport team corporate foundations. Theoretical and practical implications of these findings are discussed in the paper.